"Faith and Reason or Religion and Philosophy; The Problem of the Relationship between connection and separation from a Hermonitic Perspective" - Bakry, Jamil 'Abu Al-Abbas Zukair (Arab Journal for Sciences and Research Publishing, 2016)
Many philosophers and thinkers when they offered to the issue of the relationship between religion and philosophy have fallen into mixing error; they put all religions in one pot, until it was described religion as in other religions, at the same time it was for each of them, thinkers and philosophers, its own concept for philosophy. Therefore, This study was represented in the main question: Is there Hermeneutics problem between faith and reason, or between religion and philosophy still exists in contemporary thought? If the answer is in the affirmative, what is the way to solve them? A historical analytical method was used to assess history of an idea, in addition to critical approach with regard to the idea that require critics. As for the search tools; mainly includes mental analysis of ideas and acceptance or rejection through evidence and proof mentality in both cases.